Response of Potato Cultivars to Five Isolates Belonging to Four Strains of Potato virus Y - Nie, Bihua (Plant disease, 2012)
The responses of 14 potato cultivars to five Potato virus Y (PVY) isolates belonging to four strains (ordinary [PVYO], tobacco veinal necrosis [PVYN], N:O group [PVYN:O], and nonrecombinant potato tuber necrotic [PVYNTN]) were studied in primary and secondary infections. For the primary infection experiments, foliage symptoms were monitored daily after mechanical inoculation with a PVY isolate until harvest; and, for the secondary infection experiments, foliage symptoms were monitored regularly from plant emergence until harvest. Tuber symptoms (namely, tuber necrotic ringspots) were checked at harvest and monthly postharvest for up to 4 months. In both infections, symptoms varied significantly depending on potato cultivar and virus strain or isolate. In primary infections, local lesions occurred on inoculated leaves of 'AC Chaleur', 'Eramosa', 'Goldrush', 'Jemseg', 'Katahdin', 'Ranger Russet', and 'Yukon Gold' after inoculation with PVYO isolates, followed by systemic necrosis on latterly emerged uninoculated leaves. In contrast, plants of 'CalWhite', 'La Rouge', 'Red LaSoda', 'Russet Burbank', 'Russet Norkotah', and 'Superior' did not exhibit any visible symptoms on inoculated leaves but developed mild to severe mosaic on latterly emerged leaves after infection with PVYO isolates. In all cultivars, near-symptomless to mild mosaic was induced by PVYN and mild to severe mosaic by PVYN:O. PVYNTN induced mild to severe mosaic in plants of all cultivars except AC Chaleur, 'Cherokee', and Yukon Gold, which developed visible systemic necrosis. Necrotic ringspots were observed in tubers of PVYNTN-infected plants of AC Chaleur, Cherokee, and Yukon Gold. The tuber symptoms were also incited by PVYN-Jg on Cherokee. In secondary infections, the symptoms were generally more severe than primary infections even though the symptom types did not alter. As in the greenhouse, a clear symptom severity pattern (PVYO-FL > PVYO-RB > PVYNTN-Sl > PVYN:O-Mb58 > PVYN-Jg) was observed in AC Chaleur, Cherokee, Eramosa, Goldrush, Jemseg, Katahdin, Ranger Russet, and Yukon Gold in the field